2019
DOI: 10.1111/petr.13622
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in cell‐free DNA levels in newly transplanted heart transplant patients

Abstract: DF of cfDNA has been proposed as a stable marker for cellular injury caused by rejection in several organs including the heart. 1,2 An increased DF during episodes of rejection has been reported in both adult and pediatric heart transplant recipients. 3,4 Limited information exists regarding serial changes in DF in the immediate post-transplant phase. De Vlaminck et al 5 reports that DF declines to baseline at 1-week post-heart transplant. Similarly, in a study of DF following liver transplant, baseline levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…This has been demonstrated by comparing dd‐cfDNA with EMB in different cohorts using assays with slightly differing DNA quantification methods, and among both adult and pediatric HT recipients 18–21 . Circulating dd‐cfDNA has been shown to rise higher and appear earlier in AMR than ACR, even before perceptible findings on EMB, 18,19 and at least two reports have also found that dd‐cfDNA is elevated early after HT and falls quickly over the first 1–4 weeks 19,30 . Collectively, these data make a strong case that elevation of circulating dd‐cfDNA is a sensitive marker of allograft injury, of which AR is only one possible cause.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This has been demonstrated by comparing dd‐cfDNA with EMB in different cohorts using assays with slightly differing DNA quantification methods, and among both adult and pediatric HT recipients 18–21 . Circulating dd‐cfDNA has been shown to rise higher and appear earlier in AMR than ACR, even before perceptible findings on EMB, 18,19 and at least two reports have also found that dd‐cfDNA is elevated early after HT and falls quickly over the first 1–4 weeks 19,30 . Collectively, these data make a strong case that elevation of circulating dd‐cfDNA is a sensitive marker of allograft injury, of which AR is only one possible cause.…”
Section: Discussionmentioning
confidence: 85%
“…[18][19][20][21] Circulating dd-cfDNA has been shown to rise higher and appear earlier in AMR than ACR, even before perceptible findings on EMB, 18,19 and at least two reports have also found that dd-cfDNA is elevated early after HT and falls quickly over the first 1-4 weeks. 19,30 Collectively, these data make a strong case that elevation of circulating dd-cfDNA is a sensitive marker of allograft injury, of which AR is only one possible cause. This has generated discussion about the potential for dd-cfDNA to augment our understanding of allograft injury, 31,32 including the contribution of indolent AMR to chronic allograft loss.…”
Section: Discussionmentioning
confidence: 94%
“…In lung transplant recipients, early levels of dd-cfDNA during the first 3 months post-transplant and at the time of primary graft dysfunction are associated with the development of CLAD [28,30]. Similar trends in worse long-term outcomes associated with early dd-cfDNA levels have also been suggested in heart transplant recipients and merit further investigation [48][49][50]. The development of predictive modeling algorithms incorporating dd-cfDNA would allow for the identification of patients at risk of poor long-term outcomes.…”
Section: Future Directionsmentioning
confidence: 59%
“…Based on this decay, the GRAfT study only considered dd-cfDNA measurements beyond day 28. Knüttgen et al studied 87 patients and 770 samples using a well-validated digital droplet PCR approach [6] and showed that dd-cfDNA reached baseline earlier by one week posttransplant, similar to other studies [6,12–14]. In the GRAfT Study, dd-cfDNA showed an AUC of 0.92 to detect acute rejection, a composite endpoint of AMR and ACR [8 ▪▪ ].…”
Section: Dna-based Markersmentioning
confidence: 70%